2017
DOI: 10.1111/ijlh.12660
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different storage times at room temperature of unspun citrated blood samples on routine coagulation tests results. Results of a bicenter study and review of the literature

Abstract: Summary Introduction A maximum delay between blood collection and coagulation testing of 4 hours is recommended by most guidelines. As information on optimal storage times is limited, we investigated the potential effect of different storage times of unspun tubes, that is, ≤2, 4, 6, and 8 hours, on routine coagulation test results. Methods Four evacuated polymer tubes containing 0.109 mol/L tri‐Na citrate were drawn from 144 patients, including 39 patients on vitamin K‐antagonists. Except for storage time, all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 37 publications
1
28
1
Order By: Relevance
“…We have considered a difference of ± 0.10 μg/mL between fresh and stored samples as acceptable and also calculated percentage change in argatroban plasma level concentrations as acceptable stability from the baseline result as the in‐house reproducibility of HTI has CV's of 2.9%‐4.6%. However, discrepancy in the results is defined for this data as a test result that would have changed the therapeutic impact due to its storage induced change that is whole blood at room temperature for 24 hours this is in keeping with the recent paper by Toulon et al . Although statistically significant changes observed, these were not clinically relevant as the result would not have changed the patient's treatment.…”
Section: Discussionsupporting
confidence: 63%
“…We have considered a difference of ± 0.10 μg/mL between fresh and stored samples as acceptable and also calculated percentage change in argatroban plasma level concentrations as acceptable stability from the baseline result as the in‐house reproducibility of HTI has CV's of 2.9%‐4.6%. However, discrepancy in the results is defined for this data as a test result that would have changed the therapeutic impact due to its storage induced change that is whole blood at room temperature for 24 hours this is in keeping with the recent paper by Toulon et al . Although statistically significant changes observed, these were not clinically relevant as the result would not have changed the patient's treatment.…”
Section: Discussionsupporting
confidence: 63%
“…We studied the stability of aliquoted plasma samples stored at RT for up to 48 hours. Several studies have investigated the stability of coagulation parameters, mainly routine haemostasis parameters, in different storage conditions; however, information regarding the stability of coagulation factors studied for up to 48 hours is scarce …”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] We studied the stability of aliquoted plasma samples stored at RT for up to 48 hours. Several studies have investigated the stability of coagulation parameters, mainly routine haemostasis parameters, in different storage conditions [7][8][9][10]13,16 ; however, information regarding the stability of coagulation factors studied for up to 48 hours is scarce. 6 According to our knowledge, no published guidelines, defining acceptable percentage changes for clinically relevant difference compared with baseline values, are available.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a shorter centrifugation time will be indeed useful in emergency settings to reduce the TAT. The samples can be kept at room temperature for up to 8 h and at 4 C for up to 24 h (unspun citrated blood samples) before measurement of D-dimer [4,46,47]. Elf et al centrifuged blood samples at 4 C and measured D-dimer with two quantitative immunoassays (Innovance V R and AxSYM V R (Abbott, USA)) [48], although there was no evidence supporting cold centrifugation for D-dimer testing.…”
Section: Centrifugationmentioning
confidence: 99%
“…In brief, D-dimer is stable for at least 24 h (in plasma/whole blood) at room temperature (RT) or at 2-8 C with many different D-dimer immunoassays. Only B€ ohm-Weigert et al and Toulon et al suggested, respectively a 6-and 8-h D-dimer plasma stability, but this was because they did not extend their analysis for longer periods [47,69]. Frozen samples may also be used when longer storage periods (i.e.…”
Section: Stability Storage and Freeze-thaw Effectsmentioning
confidence: 99%